STATUS ANAK NIKAH SIRI ( PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIP ) - - - Musfira (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2017)
Marriage is something sacred act, meaningful worship to Allah SWT, following the sunnah of the Prophet and done with conscious and sincerity. Siri marriages very existence from time to time which basically aims to keep the wedding so that there are certain parties who are not known to the nuptials. Meaning of siri marriage meaning of the context of Islamic teachings therein are substantively wedding deficiencies terms and harmonious marriage although secara formal met. Series called marriage because marriage was held in secret, closed, secretive and furtive without any publicity. Even appearancesiri marriages increasingly prevalent done for a reason, without a guardian of women and even without witness and without parental female consent. a marriage is parties like this are not legitimate religion let alone legally State, Even though in practice there are many people who still distinguish where the wedding according to Islamic law and where the marriage according to the legal terms used by the people of Indonesia. Siri marriage is a marriage that makes the vagueness of the law in Indonesia is because the loss of my wife and child rights. Marriages must be justified by religion and law are positive, for the sake of administrative order and kemashlahatan people.